Temporal Effects of Sleeve Gastrectomy on Glucose-Insulin Homeostasis and Incretin Hormone Response at 1 and 6 Months - Sarah Prior (Obesity Surgery, 2020)
BackgroundBariatric surgery is an effective treatment for morbid obesity and glycaemic dysfunction.ObjectivesThe aim of the work was to examine both the static and dynamic changes of glucose-insulin homeostasis and incretin hormone response following sleeve gastrectomy (SG) in a sample of 55 participants preoperatively and 1 month and 6 months postoperatively. The focus was on a sample of patients with impaired glucose tolerance and type 2 diabetes (T2D).SettingMorriston Hospital, UK.MethodsProspective study comprising of 55 participants with impaired glucose homeostasis and T2D undergoing SG (mean body mass index [BMI] 50.4 kg/m2, mean glycated haemoglobin [A1C] 7.4%). Serial measurements of glucose, insulin, C-peptide, glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic hormone (GIP) were performed during oral glucose tolerance testing preoperatively and 1 and 6 months postoperatively. Areas under the curve (AUC) were examined at 30, 60, and 120 min.ResultsWe observed significant improvements in measures of obesity, as well as static and dynamic measures of glucose, insulin, C-peptide and HOMA. Furthermore, significant increases in GLP-1 response as early as 6 months postoperatively were also seen.ConclusionsTo our knowledge, no study has examined the detailed dynamic changes in glucose and insulin homeostasis in this number of participants undergoing SG in relation to incretin hormones GIP and GLP-1. This current study supports the role of SG for the treatment of obesity-related glucose dysregulation.